2016
DOI: 10.3917/sta.111.0043
|View full text |Cite
|
Sign up to set email alerts
|

Discours interne en contexte sportif : synthèse critique des connaissances

Abstract: Le discours interne est une habileté mentale utilisée par les athlètes afin d’optimiser la performance sportive et le bien-être psychologique. Depuis une trentaine d’années, de plus en plus de chercheurs s’intéressent au discours interne en contexte sportif. Les résultats des études effectuées dans différents sports et auprès d’athlètes de différents niveaux compétitifs révèlent que le discours interne a une influence sur la performance sportive. Certains résultats équivoques invitent toutefois à se pencher su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
2
2
0
1
Order By: Relevance
“…Initially, the results of this study show a beneficial effect of positive motivational internal discourse on the percentage of successful first service balls, whereas that of players in the control group remained stable. These results, which validate our first hypothesis, also confirm the results of previous studies that have shown beneficial effects of internal discourse on sports performance (Boudreault et al, 2016;Theodorakis et al, 2000), particularly in tennis (Fristch et al, 2020;. As mentioned by Landin and Hebert (1999), we could envisage that positive motivational internal discourse would increase players' self-confidence, which would enable them to increase their percentage of successful first service balls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Initially, the results of this study show a beneficial effect of positive motivational internal discourse on the percentage of successful first service balls, whereas that of players in the control group remained stable. These results, which validate our first hypothesis, also confirm the results of previous studies that have shown beneficial effects of internal discourse on sports performance (Boudreault et al, 2016;Theodorakis et al, 2000), particularly in tennis (Fristch et al, 2020;. As mentioned by Landin and Hebert (1999), we could envisage that positive motivational internal discourse would increase players' self-confidence, which would enable them to increase their percentage of successful first service balls.…”
Section: Discussionsupporting
confidence: 91%
“…These verbalisations can be spontaneous (uncontrolled) or strategic (linked to a predetermined objective) as mentioned by Van Raalte et al (2016). Strategic internal discourse is a deliberate mental technique frequently used by practitioners to optimise performance by means of its cognitive function, which is generally technique-oriented (e.g., "Straighten your arm", "Bend your legs", "I have to finish my gesture") and which will help guide the execution of movements in beginners (Boudreault et al, 2016). Internal discourse can also be used to regulate the emotions of more experienced players through its motivational function (Fristch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The latter results confirm those of previous studies, which have shown the beneficial effects of combining different mental strategies (e.g., MI and self-talk) on tennis performance (Mamassis and Doganis, 2004;Dohme et al, 2020). In addition, these results seem to show the beneficial benefits of the motivational function of goal-directed self-talk (Hardy et al, 2015;Zourbanos et al, 2015;Boudreault et al, 2016;Fritsch et al, 2020), especially when this technique is combined with MI (Dohme et al, 2020). As suggested by Landin and Hebert (1999), we may postulate that the use of self-talk could increase the self-confidence of the participants of the MI + self-talk group inducing greater service efficiency and points won than the participants of the other groups.…”
Section: Discussionsupporting
confidence: 91%
“…It generally concerns past events (e.g., "that was a bad shot") or future outcomes (e.g., "I will win"). The goaldirected self-talk is a deliberate mental technique or strategies frequently used by athletes to optimize performance utilizing its cognitive function (Boudreault et al, 2016) or regulate emotions by means of its motivational function (Fritsch et al, 2020). Cognitive or instructional self-talk aims to improve performance by means of an attentional focus directed toward technique (e.g., "bending the knees") or necessary motor actions (e.g., "getting back on the court"), whereas motivational self-talk can be employed to proactively and reactively regulate motivation, self-confidence, and emotion (e.g., "enjoy your game") or to sustain effort (e.g., "I will play well in the next set").…”
Section: Introductionmentioning
confidence: 99%
“…Par exemple, ils se disent « vas-y, tu es capable », « hop » ou « pousse les poignets », « je ne suis plus capable » ou « plus vite, plus vite ». Ce langage intérieur est désigné en psychologie du sport comme discours interne (self talk) (Boudreault, Trottier & Provencher, 2016 ;Hardy, 2006 ;Hardy, Gammage & Hall, 2001 ;Hatzigeorgiadis, Zoubanos, Galanis & Theodorakis, 2011). Le discours interne possède trois propriétés : 1) il est interprétatif, car formé par du langage, 2) il réalise au moins deux fonctions : cognitive et motivationnelle et 3) la dyade émetteur-récepteur est la même personne (Latinjak, Hatzigeorgiadis, Comoutos & Hardy, 2019).…”
Section: Introductionunclassified